2‐Ethylsulfanyl‐7‐(furan‐2‐yl)‐4‐(thiophen‐2‐yl)pyrazolo[1, 5‐a][1, 3, 5]triazine: π‐stacked chains of hydrogen‐bonded R22(10) dimers. Issue 9 (26th August 2014) - Insuasty, Henry; Insuasty, Braulio; Castro, Edison; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title compound, C15H12N4OS2, the bond distances in the fused heterocyclic system show evidence for aromatic‐type delocalization in the pyrazole ring with some bond fixation in the triazine ring. The thiophenyl substituent is slightly disordered over two sets of atomic sites having occupancies of 0.934 (4) and 0.066 (4). The non‐H atoms in the entire molecule are nearly coplanar, with the planes of the furanyl substituent and the major orientation of the thiophenyl substituent making dihedral angles of 5.72 (17) and 1.8 (3)°, respectively, with that of the fused ring system. Molecules are linked into centrosymmetric R22(10) dimers by C—H...O hydrogen bonds and these dimers are further linked into chains by a single π–π stacking interaction. Comparisons are made with some related 4, 7‐diaryl‐2‐(ethylsulfanyl)pyrazolo[1, 5‐a][1, 3, 5]triazines which contain variously substituted aryl groups in place of the furanyl and thiophenyl substituents in the title compound.